2021
DOI: 10.36227/techrxiv.14994444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elastic O-RAN Slicing for Industrial Monitoring and Control: A Distributed Matching Game and Deep Reinforcement Learning Approach

Abstract: In this work, we design an elastic open radio access network (O-RAN) slicing for the industrial Internet of things (IIoT). Unlike IoT, IIoT poses additional challenges such as severe communication environment, network-slice resource demand variations, and on-time information update from the IIoT devices during industrial production. First, we formulate the O-RAN slicing problem for on-time industrial monitoring and control where the objective is to minimize the cost of fresh information updates (i.e., age of i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In Table 10, we categorize the reviewed proposals based on the ML technique and the type and number of used algorithms. According to our analysis of the literature review on resource management in RAN slicing, as shown in T-NN 1 Evolutionary Algorithms [65], [66], [68], [69], [67], [70], [72], [71] GA 8 [35], [79], [80], [81], [129], [130], [95] AC 7 [78] MAB 1 [111], [85], [117], [86], [87], [88], [136], [90], [96], [97], [98], [151], [126], [99], [123], [131], [114], [118], [94], [100], [103], [119], [104], [105] DQN 25 [109], [108] Q-Learning 2 Reinforcement Learning [115], [112], [84] Double DQN 3 …”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Table 10, we categorize the reviewed proposals based on the ML technique and the type and number of used algorithms. According to our analysis of the literature review on resource management in RAN slicing, as shown in T-NN 1 Evolutionary Algorithms [65], [66], [68], [69], [67], [70], [72], [71] GA 8 [35], [79], [80], [81], [129], [130], [95] AC 7 [78] MAB 1 [111], [85], [117], [86], [87], [88], [136], [90], [96], [97], [98], [151], [126], [99], [123], [131], [114], [118], [94], [100], [103], [119], [104], [105] DQN 25 [109], [108] Q-Learning 2 Reinforcement Learning [115], [112], [84] Double DQN 3 …”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…The simulation results demonstrate that the Spectrum Efficiency in DRL is higher than the proportionally fair, water-filling, and round-robin allocation methods for eMBB, uRLLC, and mMTC slices. The authors of [95] have proposed an elastic method based on distributed game theory and RL to allocate resources in a macro-cell BS within O-RAN to meet the needs of three different classes of Industrial IoT. In this approach, the authors aimed to balance the age of information (AoI) and energy efficiency while maximizing service rates using synchronization between multiple devices.…”
Section: ) Resource Sharingmentioning
confidence: 99%
See 2 more Smart Citations
“…Each objective must capture the requirements and requests of industrial applications realistically using critical metrics as service rate, scheduling and isolation, information freshness, and energy efficiency. In this direction, in [151], using distributed game theory and machine learning, the authors developed an elastic network slice policy to satisfy time-varying resource allocation demands for three different industrial traffic classes. In the slice configuration policy, the authors mainly aimed to balance AoI and energy efficiency while maximizing the service rate.…”
Section: G-and-beyond/6g Network and Aoi-aware Green Communicationmentioning
confidence: 99%